Embryology of Swainsona formosa (Fabaceae): Anther and Ovule Development - ZULKARNAIN ZULKARNAIN (Bogor Agricultural University, Indonesia, 2005)
Our study showed that floral morphology and anatomy in Swainsona formosa were typical of leguminous flower. The anthers were found to be tetrasporangiate, with a 3-layered wall below the epidermis. The wall was comprised of a layer of endothecium, middle layer and secretory tapetum. Pollen grains were triporate and shed at a two-cell stage. The ovules were campylotropous with a zigzag micropyle. Multiple embryo sacs were occasionally found but only one mature embryo was formed in the seed. Rubbing the receptive stigma with fingertip enhanced pollination, resulted in 100% pod formation on treated flowers. During fertilization, the pollen tube entered the embryo sac via one of two existing synergids, destroying the synergid in the process. The endosperm was of nuclear type, and only one or two layers of endosperm left as the seed reached its maturity. The seed coat was composed of a single layer of thick-walled palisade cells on the outside followed by a single layer hypodermal sclereids on the inside.